Synthesis, spectroscopic findings, SEM/EDX, DFT, and single-crystal structure of Hg/Pb/Cu–SCN complexes: In silico ADME/T profiling and promising antibacterial activities - Dhrubajyoti Majumdar; Jessica Elizabeth Philip; Amit Dubey; Aisha Tufail; Sourav Roy (Heliyon, 2023)
This work contemplates synthesizing M-SCN crystal compounds (M = Hg/Pb/Cu) in the presence of respective metal salts and exogenous ancillary SCN− ion by slowly evaporating the mixed solvent (CH3OH + ACN). The complexes were characterized by spectroscopy, SEM/EDX, and X-ray crystallography. The Hg-Complex, Pb-Complex, and Cu-Complex crystallize in the monoclinic space group (Z = 2/4). The crystal packing fascinatingly consists of weak covalent bonding and Pb⋯S contacts of tetrel type bond. Here are the incredible supramolecular topographies delineated by the Hirshfeld surface and 2D fingerprint plot. The B3LYP/6–311++G (d, p) level calculations in the gas phase optimized the compound's geometry. The energy difference (Δ) between HOMO-LUMO and global reactivity parameters investigates the complex's energetic activity. MESP highlights the electrophilic/nucleophilic sites and H-bonding interactions. Molecular docking was conceded with the Gram- + ve bacterium Bacillus Subtilis (PDB ID: 6UF6) and the Gram-ve bacterium Proteus Vulgaris (PDB ID: 5HXW) to authenticate the bactericidal activity. ADME/T explains the various pharmacological properties. In addition, we studied the antibacterial activity with MIC (μg/mL) values and time-kill kinetics against Staphylococcus aureus (ATCC 25923) and Bacillus subtilis (ATCC 6635) as Gram-positive, Pseudomonas aeruginosa (ATCC 27853) and Escherichia coli (ATCC 25922) as Gram-negative bacteria.